Fuzzy Automatic Control of the Pyrolysis Process for the Municipal Solid Waste of Variable Composition - Kondratenko, Yuriy; Kozlov, Oleksiy; Lysiuk, Hanna; Kryvda, Viktoriia; Maksymova, Oksana (Journal of Automation, Mobile Robotics and Intelligent Systems, 2023)
control of the pyrolysis process of municipal solid waste (MSW) of variable composition and moisture content. The fuzzy control method is developed and studied that makes it possible to carry out the proper automatic control of the pyrolysis plant with the determination of the optimal ratio of air/MSW for various types of waste and with different moisture content values to ensure high efficiency of the MSW disposal process. The effectiveness study of the proposed fuzzy control method is performed in this paper on a specific example, in particular, when automating the pyrolysis plant for the MSW disposal with the reactor volume of 250 liters. The obtained simulation results confirm the high efficiency of the developed method, as well as the feasibility of its use for designing automatic control systems of various pyrolysis plants that operate under conditions of changes in the composition and moisture content of input waste.